A randomised, prospective study of the effects of 3% diquafosol on ocular surface following cataract surgery - Sangyoon Kim (Nature Portfolio, 2021)
Abstract There is still no established therapeutic solution for postoperative Dry Eye Syndrome (DES) after cataract surgery, in spite of progress in surgical techniques. Diquafosol tetrasodium (DQS), a recently developed ophthalmic solution, has been reported to be effective in DES, but no study evaluated post-cataract surgery lipid layer thickness (LLT) changes in healthy patients who used DQS postoperatively. We randomly divided participants into two groups; the DQS group was treated six times daily with DQS after cataract surgery, and the sodium hyaluronate (HA) group was treated with HA in the same way. Throughout study period, the DQS group showed significantly higher tear break up time (TBUT) and LLT than HA group. In multivariate analysis, better preoperative TBUT, Schirmer’s I test score, ocular surface disease index (OSDI) score, and LLT were significantly associated with improved postoperative outcomes in each parameter. Also, the postoperative use of DQS served as an independent parameter of better TBUT, OSDI score, and LLT in postoperative 15 weeks. Treatment with 3% DQS following cataract surgery showed more improvement in TBUT and LLT, compared with 0.1% HA. Improving TBUT and LLT preoperatively and using 3% DQS postoperatively, could be a reliable choice for managing DES after cataract surgery. Trial Registration: ISRCTN registry with ISRCTN 18755487.